Allama Iqbal Open University's "Department of Pakistani Languages", Punjabi and National Language - Latif, Wasif (Makhz (Research Journal), 2025)
Allama Iqbal Open University was established in May 1974 while in addition to various departments of the university, the "Department of Pakistani languages" was started in 1998 for the development and promotion of regional languages with the aim of promoting national unity and national harmony, informing students about the common impressions of Pakistani languages and inter linguistics coordination to enhance the sphere of understanding and knowing. The connections and common literary introduction and tendencies were to be highlighted. After that M. Phil and Ph. D programs from the same department were also started and are running very successfully up till now. The medium of instruction in the "Department of Pakistani Languages" which deals with 18 languages, which is also national and official language of Pakistan. So, a research scholar has the option to write his research thesis in English or Urdu in addition to his regional language. With the establishment of this department, where the opportunities for the advancement of higher education and high-grade research in regional languages become possible. So, due Urdu language all the work done in terms of curriculum development and research activities are Urdu language and literature also got a boost. In this article, the services of the "Department of Pakistani languages" with respect to Punjabi language and literature are discussed and analyzed through which the prominent role of this department for the promotion of national language gains immense importance.